2019
DOI: 10.1097/prs.0000000000005371
|View full text |Cite
|
Sign up to set email alerts
|

Round versus Anatomical Implants in Primary Cosmetic Breast Augmentation: A Meta-Analysis and Systematic Review

Abstract: Background: Choosing implant shape (round or anatomical) is one of the most essential yet controversial decisions in cosmetic breast augmentation. Many surgeons choose implant shape based on personal experience or expert opinion. This is the first systematic review and meta-analysis comparing the aesthetic effect between anatomical and round implants in primary cosmetic breast augmentation. Methods: The authors searched the PubMed, MEDLINE, Embase, Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The essential finding that round and anatomical implants have neither significant effect on the topography of single breast quadrants, nor on the entire topography of the breast, is concordant with findings in previous studies on the subjective perception of these effects [ 7 , 8 , 9 , 19 , 25 ]. The volumetric impact of all breast implants was mainly in quadrant II, followed by I, III, and IV.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The essential finding that round and anatomical implants have neither significant effect on the topography of single breast quadrants, nor on the entire topography of the breast, is concordant with findings in previous studies on the subjective perception of these effects [ 7 , 8 , 9 , 19 , 25 ]. The volumetric impact of all breast implants was mainly in quadrant II, followed by I, III, and IV.…”
Section: Discussionsupporting
confidence: 89%
“…These recordings support the surgeons in their planning and decision-making [ 1 , 2 , 3 , 4 , 5 , 6 ]. The choice of the appropriate implant has been discussed in several studies as one of the most important factors affecting the postoperative appearance of the breasts after augmentation [ 7 , 8 , 9 ]. Due to the lack of comparison between different implant shapes and volumes in the same patient [ 7 , 8 ] and the limited use of accurate measurements [ 9 ] obtained from photography, which can only reproduce the topography of the breast to a limited extent, data are not sufficient to enable an evidence-based choice of the most suitable implant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another effort to overcome some of the other morphological differences, implant choice might play a more defining role in trans women. Although discussions on the aesthetic outcomes and distinguishability of implant shapes in cis women have been long and ongoing, a recent anthropometric study showed that round and anatomically shaped implants influence breast morphology differently [7,17,24,26]. A cadaver study showed that anatomically shaped implants were more adept at creating a longer IMF-N, and to a lesser extent, lengthening the SN-N too [14].…”
Section: Discussionmentioning
confidence: 99%
“…(3D) surface body measurement have offered new possibilities to numerically assess the female breast [1,2,[6][7][8][9][10][11][12][13][14][15][16]. These technologies are characterized by significantly faster data acquisition compared with linear and circumference measurements, water displacement and other conventional methods [11,14].…”
Section: Introductionmentioning
confidence: 99%